Amplifying Tumor–Stroma Communication: An Emerging Oncogenic Function of Mutant p53 - Capaci, Valeria; Mantovani, Fiamma; Del Sal, Giannino (Frontiers in Oncology, 2021)
TP53 mutations are widespread in human cancers. An expanding body of evidence highlights that, in addition to their manifold cell-intrinsic activities boosting tumor progression, missense p53 mutants enhance the ability of tumor cells to communicate amongst themselves and with the tumor stroma, by affecting both the quality and the quantity of the cancer secretome. In this review, we summarize recent literature demonstrating that mutant p53 enhances the production of growth and angiogenic factors, inflammatory cytokines and chemokines, modulates biochemical and biomechanical properties of the extracellular matrix, reprograms the cell trafficking machinery to enhance secretion and promote recycling of membrane proteins, and affects exosome composition. All these activities contribute to the release of a promalignant secretome with both local and systemic effects, that is key to the ability of mutant p53 to fuel tumor growth and enable metastatic competence. A precise knowledge of the molecular mechanisms underlying the interplay between mutant p53 and the microenvironment is expected to unveil non-invasive biomarkers and actionable targets to blunt tumor aggressiveness.